“There Are Things We Can Do and There Are Things We Cannot Do.” A Qualitative Study About Women's Perceptions on Empowerment in Relation to Fertility Intentions and Family Planning Practices in Mozambique - Castro Lopes, Sofia; Constant, Deborah; Fraga, Sílvia; Osman, Nafissa Bique; Harries, Jane (Frontiers in Global Women's Health, 2022)
Introduction The restrictive socio-cultural norms in Mozambique limit the power of women to decide, voice, and act on their reproductive choices. This study aimed to explore women’s perceptions and experiences of empowerment relating to fertility intentions and family planning practices in Mozambique, focusing on facilitators and barriers towards reproductive empowerment. Methods Qualitative in-depth interviews were undertaken with women of reproductive age (18-49 years) in Nampula and Maputo provinces and Maputo city, Mozambique. Data collection took place between February and March 2020 in Maputo region and during August 2020 in Nampula Province. Convenience sampling was used to recruit participants from both urban and rural healthcare facilities and from within the communities serving the healthcare facilities. In Maputo city, a snowball sampling technique was used to recruit women from the community. A total of 64 women were interviewed, 39 from Maputo and 25 from Nampula. A thematic analysis was conducted with the support of NVivo12 software. Results Several factors that hinder and facilitate women’s empowerment towards fertility and family planning practices in Mozambique were identified and were interpreted within the socio-ecological model. The identified barriers included women’s lack of critical consciousness and oppressive relationships. At the community and societal levels, the role of traditions, culture and gender expectations and limited access to family planning and misinformation were also important hindering factors. The facilitators of reproductive empowerment included building critical consciousness and access to economic resources at the individual level. Negative experiences at the household level were triggers of women’s empowerment for family planning. Building collective power and access to information, including education, were key at the community and societal levels. Conclusions This study identified various factors that positively or negatively influence women’s empowerment journeys in Mozambique. The role of tradition, culture, and gender expectations, and oppressive relationships, were important barriers in both provinces. Women from rural areas would benefit from building of consciousness about their rights, and power to decide on their reproductive lives. Interactions with the health providers offer an opportunity to do this by favoring controlling behaviors concerning their reproductive lives, promoting social networking and levering collective power.